2010
DOI: 10.1111/j.1476-8070.2010.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes and Practices that Shape Children's Drawing Experience at Home and at School

Abstract: Concept: Few empirical studies have investigated the influence of teachers, parents and children on children's drawing experience. The current study aims to examine the attitudes and practices of these three key players that shape children's drawing experience. Method: A survey methodology was used, as typically found in previous research in this area. Participants were 270 5–14 year old children, 44 of their teachers of the National Curriculum for Art and Design, and 146 of their parents. The teachers and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 16 publications
3
67
1
6
Order By: Relevance
“…In Hsiao's (2010) study, it also showed that, after conducting a series of picture book courses, parents had a highly positive attitude towards children's art making experience and artworks. Moreover, Burkitt et al (2010) mentioned parents who recommend that art education should be integrated with other taught subjects. Most Taiwanese preschool teachers implemented a theme-based curriculum and integrated art activities with other subjects to obtain the best learning effects.…”
Section: Comprehensive Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hsiao's (2010) study, it also showed that, after conducting a series of picture book courses, parents had a highly positive attitude towards children's art making experience and artworks. Moreover, Burkitt et al (2010) mentioned parents who recommend that art education should be integrated with other taught subjects. Most Taiwanese preschool teachers implemented a theme-based curriculum and integrated art activities with other subjects to obtain the best learning effects.…”
Section: Comprehensive Discussionmentioning
confidence: 99%
“…However, only a few studies, most of which primarily targeted "after-school art classes", have explored the parents of these children. Some western researchers have proved that significant differences in the beliefs of children art education between parents of different background factors (Anning, 2002;Burkitt, Jolley, & Rose, 2010;Elliot, 1987;Huntsinger, Jose, Krieg, & Luo, 2011;Kantner & Hoffman,1992;Rose, Jolle, & Burkitt, 2006). There are still several stages concerning preschool art education that remain to be clarified in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Burkitt, Jolley and Rose (2010) interviewed and surveyed parents, teachers and children to explore children's drawing experience. This large scale research involved collecting data from 29 English schools (primary and secondary).…”
Section: What Do Children Think?mentioning
confidence: 99%
“…The process of drawing promotes many psychological benefits for children, including visual thinking, observation and the analysis of subject matter, problem solving, imagination, expression, creativity, as well as more general habits of thinking such as perseverance, experimentation and reflection (Arnheim, 1969;Barnes, 2002;Burkitt, Rose & Jolley, 2010;Hetland, Winner, Veenema & Sheridan, 2013). Furthermore, producing the artefacts develops children's drawing ability, both for their representational drawing of the subjects depicted and their expressive drawing of emotional/conceptual messages.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the analyses yielded a U-shaped curve in the merit of expressive drawings when those scores were statistically adjusted by realism drawing performance: young children and adolescent/adult sample showed elevated merit, more notably the later sample when artists were considered. The findings suggest the previously reported age-incremental patterns were influenced by a consideration of realism drawing ability in the assessment, while the Ushape curve de-emphasises representational realism in the content of the drawings.Expressive Drawing Development Linear U-shape Linear and U-shape trends 3 Linear and U-shape trends in the development of expressive drawing from pre-schoolers to normative and artistic artistsThe process of drawing promotes many psychological benefits for children, including visual thinking, observation and the analysis of subject matter, problem solving, imagination, expression, creativity, as well as more general habits of thinking such as perseverance, experimentation and reflection (Arnheim, 1969;Barnes, 2002;Burkitt, Rose & Jolley, 2010;Hetland, Winner, Veenema & Sheridan, 2013). Furthermore, producing the artefacts develops children's drawing ability, both for their representational drawing of the subjects depicted and their expressive drawing of emotional/conceptual messages.…”
mentioning
confidence: 99%